Improvement Of Polyhydroxyalkanoate Synthase From Wautersia Eutropha By In Vitro Evolution - Mohd Yahaya, Normi (2005)
The key enzyme in PHB biosynthesis of the bacterium Wautersia eutropha is PHA synthase.